A Cadaveric Study on the Morphology and Congenital Anomalies of the Liver - Agamdeep Singh Bedi; Akash Chopra; Adya Khanna; Shilpa M. Bhimalli (Journal of the Scientific Society)
Introduction: The liver is a large, wedge-like abdominal organ which occupies the right and left hypochondriac, epigastric regions. Anatomically, the liver is divided into right and left lobes by the falciform ligament anteriorly, fissure of ligamentum teres inferiorly, and fissure for ligamentum venosum posteriorly. The right lobe includes the caudate and quadrate lobes. Aim: The aim of the study was to study the morphological variations and congenital anomalies of the human liver. Materials and Methods: From the Department of Anatomy, KAHER’s J. N. Medical College, Belagavi, 40 human adult livers were obtained from cadavers of both sexes. They were classified based on their morphology, and a few anomalies were also observed. Results: Based on the data collected, livers were classified according to Netter’s classification based on morphology: • Type 1 – 5/40 • Type 2 – 0/40 • Type 3 – 2/40 • Type 4 – 7/40 • Type 5 – 4/40 • Type 6 – 9/40 • Normal: 13/40 • Congenital anomalies found • Monocystic liver: 1/40 • Agenesis of quadrate lobe: 3/40 • Fusion of quadrate and left lobe-4/40. Conclusion: Knowing about the variations of liver morphology will help clinicians avoid diagnostic errors. This helps prevent fatal surgical complications and will help in planning appropriate surgical approaches.